2015
DOI: 10.1038/gt.2015.63
|View full text |Cite
|
Sign up to set email alerts
|

The spread of adenoviral vectors to central nervous system through pathway of cochlea in mimetic aging and young rats

Abstract: There is no definitive conclusion concerning the spread of viral vectors to the brain after a cochlear inoculation. In addition, some studies have reported different distribution profiles of viral vectors in the central auditory system after a cochlear inoculation. Thus, rats were grouped into either a mimetic aging group or a young group and transfected with adenoviral vectors (AdVs) by round window membrane injection. The distribution of AdV in central nervous system (CNS) was demonstrated in the two groups … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 69 publications
0
6
0
Order By: Relevance
“…The brains were removed and postfixed in 4% paraformaldehyde overnight at 4 °C. The selection and orientation of the auditory cortex and the following procedures were previously published [33]. Primary antibodies against cleaved-caspase-3 (1:500, servicebio, Wuhan, Hubei, China) and glial fibrillary acidic protein (GFAP; 1:1000, Proteintech, Wuhan, Hubei, China) were used for the IHC analysis.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…The brains were removed and postfixed in 4% paraformaldehyde overnight at 4 °C. The selection and orientation of the auditory cortex and the following procedures were previously published [33]. Primary antibodies against cleaved-caspase-3 (1:500, servicebio, Wuhan, Hubei, China) and glial fibrillary acidic protein (GFAP; 1:1000, Proteintech, Wuhan, Hubei, China) were used for the IHC analysis.…”
Section: Methodsmentioning
confidence: 99%
“…The Nissl staining analysis was performed according to our published paper with few modifications [33]. Briefly, serial transverse sections made from paraffin-embedded brains were dewaxed with xylene, followed by rehydration in graded alcohol and immersion in 0.3% toluidine blue for 40 min at 60 °C.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Although initial studies showed substantial dose-and time-dependent hair cell toxicity (Dazert et al 1997;Holt et al 1999;Luebke et al 2001a), multiply deleted (E1 − , E3 − , pol − , pTP − ) adenoviruses without impaired viral infectivity (Holt 2002) preserved cochlear function and hair cell transduction (Luebke et al 2001b;Holt 2002;Corey et al 2004). However, because of their potential immunogenicity, cell toxicity, and possible CNS virus spread (Chen et al 2015), future use of adenoviruses is under further investigation. Newer development of adenoviruses, mainly using helper-dependent adenoviruses (Wenzel et al 2007) or different serotypes (Ad28) additionally supported their potential use in future cochlear gene therapy (Kraft et al 2013).…”
Section: Adenovirusesmentioning
confidence: 99%